Doing business in Second Life: e-commerce in 3D online environment. (10th March 2010) - Zhang, Dongsong; Shrestha, Prabodh
Avatar-based 3D virtual worlds provide an unprecedented environment for e-commerce that potentially allows online shoppers to have similar shopping experience as they have in physical stores. However, existing 3D virtual worlds are lack of critical components for successful e-commerce. Second Life is the only 3D platform that currently enables a user to operate a virtual business with real earnings. In this paper, we analyse the Second Life as a 3D e-business environment. We propose a conceptual framework and discuss the possibility of adapting the traditional 2D e-commerce architecture to the 3D virtual world.